PERANCANGAN ALAT UJI TEKUK SEDERHANA - Kurniawan Arief, Rudi (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Effeciency, effectiveness and productivity can be increased by adoptation of technology thru understanding physical phenomenon. Buckling is a physical phenomenon that must be avoid in any structures built. In mechanical engineering this buckling test is learned as a laboratorium practice. Bucling test equipment unit is available in the market but with high price, thus we try to design and build a simple yet cheap bucling test unit. The unit consist of Pressure gauge and Dial indicator to get exact value of deflection dan pressure / force given. Some students also involved during this activities.